GLP1 receptor agonists and their role in the therapy of neurodegenerative diseases - a literature review - Kuna, Paweł Jan; Borowski, Konrad; Chmielowiec , Laura; Radziwon, Maja; Kuna, Wojciech; Chojniak, Alicja; Łyko, Zuzanna; Tomaszek, Michał; Benecka, Agnieszka; Sikora, Artur (Quality in Sport, 2026)
Introduction: GLP-1 receptor agonists (GLP-1RAs) are drugs used in the treatment of type 2 diabetes and obesity, and are believed to have potential neuroprotective properties. Decreased glucose metabolism in the brain, the development of neuronal insulin resistance, and abnormal tau protein phosphorylation and amyloid-β deposition all play important roles in the pathogenesis of Alzheimer’s disease (AD). Numerous preclinical studies in animal models have demonstrated that GLP-1 analogs, such as liraglutide and lixisenatide, are capable of crossing the blood-brain barrier, stimulating neurogenesis, limiting tau hyperphosphorylation, reducing amyloid-β deposition, and improving synaptic and cognitive functions. Data from clinical and observational studies suggest that GLP-1RA use in patients with type 2 diabetes is associated with a reduced risk of developing dementia, including AD. In large retrospective analyses, semaglutide therapy reduced the likelihood of a first diagnosis of Alzheimer’s disease by 40–70% compared with other antidiabetic agents. In a randomized trial, liraglutide prevented the decline in brain glucose metabolism in patients with AD, but had no significant effect on amyloid-β levels or cognitive function. Review methods: A comprehensive analysis of research papers available on PubMed and Google Scholar was conducted using keywords: Alzheimer’s disease, neurodegeneration, GLP-1 analogues, liraglutide, dementia, tau, diabetes, obesity Conclusion: Accumulating evidence suggests that GLP-1 agonists may be a promising therapeutic option for the prevention and treatment of neurodegenerative diseases. However, further randomized clinical trials are necessary to confirm their efficacy in patients with Alzheimer’s disease. Keywords: Alzheimer’s disease, neurodegeneration, GLP-1 analogues, liraglutide, dementia, tau, diabetes, obesity